PENGARUH KONSEP DIRI DAN KOMPETENSI TERHADAP KOMITMEN ORGANISASI PADA PT. BAROKAH UTAMA KARYA MEDAN - Asnora, Fadzil Hanafi; Indra, Aulia (LPPM Universitas Labuhanbatu, 2020)
From the initial research that the researchers conducted, the weakness of employees in building trust, namely interactions with other individuals and building a sense of confidence in the company. Concern and uncertainty which causes employee commitment to be disrupted, apart from the result of not being able to focus time and energy on tasks and work which results in neglected aspects of work, also because there are still employees who have not been able to accept responsibility for the work of others either positive or negative, this is because there are still employees who have not been able to formulate a criteria or work procedure to achieve the quality, productivity and work services required. The purpose of this study was to determine the effect of self-concept and competence on organizational commitment at PT. Barokah Utama Karya Medan. The number of samples in this study amounted to 93 people using saturated sampling technique. The analysis technique used is multiple linear regression. The results showed that there was no direct significant influence of self-concept on organizational commitment. Directly there was a significant influence of competence on organizational commitment.